Machinic Pleasures and Interpellations - John Law (Tecnoscienza, 2012)
How do objects interpellate us? What are the pleasures of machines? What, in particular, are the male pleasures that are made in the knowing and telling of machines? Reflecting upon a small selection of the variety of machinic pleasures, the paper considers the ecology of subject-object distribution and explores how it is we are called to become knowing subjects, and how it is that objects are constituted and known in particular ways.